Client Influence on Property Valuation: A Literature Review - Achu, Kamalahasan (Centre of Real Estate Studies, Universiti Teknologi Malaysia, 2013)
In recent years, client influence on property valuation has been an emerging theme of behavioural research in the real estate discipline. Studies on valuers’ decision-making behaviour imply that client influence is an important source of judgemental bias. Academic interest in this area, however, has evolved from the task of identifying the existence of client pressure to studies that explain the mechanism of client influence in relation to specific valuation types. This paper offers a thorough review of the existing studies on client influence with the aim to underline future research areas. The existing literature is organised and discussed under three topics: (1) client pressure evidence; (2) influences related to client characteristics; and (3) influences related to specific valuation purposes. The need for better data and methodological solutions is a major constraint and it is expected that future studies in this area would utilise both quantitative and qualitative approaches in order to explain the extent and effect of this phenomenon on valuation. The fact remains that there is much more to discover about client-valuer relationship in the workplace and more importantly its role in the valuation accuracy and variation debate.